The essential role of physician as advocate: how and why we pass it on - Luft, LeeAnne M. (Canadian Medical Education Journal, 2017)
There is consensus amongst regulatory and certifying associations that the role of physician as advocate is a fundamental competency for Canadian physicians. Understanding what advocacy is and looks like in daily practice is integral to achieving this competency. Identifying barriers and exploring how we as physicians acquire the skills of advocacy are discussed. The current state of advocacy in medical education is reviewed as the starting point for exploring how best to foster the skills of physician as advocate.